2018
DOI: 10.4236/ampc.2018.84011
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline Diamond Films Grown by Microwave Plasma Chemical Vapor Deposition and Its Biocompatible Property

Abstract: Due to its unique properties such as high hardness, light transmittance, thermal conductance, chemical stability and corrosion resistance, diamond has drawn tremendous attention in last two decades. These specific properties made diamond film a promising material for cutting tools, microwave windows, heat sinks for electronic devices and diamond electrodes. However, the diamond film with grain sizes at microscale usually exhibits high surface roughness and hinders its applications in the microelectro mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Moreover, the microwave plasma (MW) CVD is widely used to synthesize ND films on various chemically dissimilar surface substrates owing to the relatively low growth temperature, which utilizes the microwave energy to heat and decompose the gas molecules in the cavity into reactive groups, then finally obtain a high-quality ND film [ 65 , 66 , 67 , 68 , 69 , 70 ]. For example, Cheng C.Y.…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%
“…Moreover, the microwave plasma (MW) CVD is widely used to synthesize ND films on various chemically dissimilar surface substrates owing to the relatively low growth temperature, which utilizes the microwave energy to heat and decompose the gas molecules in the cavity into reactive groups, then finally obtain a high-quality ND film [ 65 , 66 , 67 , 68 , 69 , 70 ]. For example, Cheng C.Y.…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%
“…Although MPCVD has been observed as a convenient method to deposit NDC films at lower temperatures than HFCVD, it has been reported that the growth rate decreases with decreasing substrate temperature in CVD methods [14]. Moreover, contamination is more likely to happen from the filament materials, which is another drawback of HFCVD [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has applications in particle detectors, single photon emitters in quantum information technology [1,2,3]. Whereas the nanocrystalline diamonds (NCDs) find applications in field emission, tribology, passive element as heat spreading in electronic devices and optical coatings [4,5]. Even though diamond has several unmatched properties in comparison to its competing materials, still a lot challenges have to overcome in terms of growth and doping to use it in practical device applications.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced conductivity is generally assigned to increase in sp 2 -rich C=C bonding at grain boundaries (GBs) [6]. Further, N doping in NCDs enhances physical and mechanical properties which make them useful for applications in photocathode for photoinjectors [7], electrochemical devices that can work under higher potential window [8], microelectromechanical system [9], and biomedical devices [5]. Due to these several advantages of N doped NCD, the research interest on the study of N incorporation and its effects on growth, structural, electrical and optical properties of diamond is ever expanding.…”
Section: Introductionmentioning
confidence: 99%